Keanekaragaman Hymenoptera Parasitoid Pada Pertanaman Padi di Dataran Rendah dan Dataran Tinggi Sumatera Barat - Delci Ariani Jasrani; Hidrayani Hidrayani; Zahlul Ikhsan (Fakultas Pertanian, Program Studi Agroteknologi, 2016)
Hymenoptera parasitoids are potential as biological agents for controlling insect pests of rice plant. Diversity of hymenoptera parasitoids was studied in low and high land rice plant in west Sumatra. Objective of research was to obtain information about diversity and equity of hymenoptera parasitoids in ecosystem of low and high land rice. A survey was conducted using purposive random sampling. Collection of insects was done using insects net and yellow pan traps. The number of hymenoptera parasitoids found in rice plant in the lowland was 114 individuals which belonged to 10 families and 29 species, and in highland there were 112 individuals which belonged to 13 families and 31 species. Diversity and evenness index of hymenoptera parasitoid species were slightly higher in highland (3.198 and 0.922) compared to low land (3.029 and 0.890)